A Study of Feminism in Ihan Sunrise's Rihon Short Story Book - Kasmi, Hendra; Mahmud, Teuku; Harfiandi, Harfiandi; Simatupang, Yusrawati JR; Nasution, Wahidah; Kustina, Rika (Teunuleh Publisher, 2023)
This research focuses on the influence of feminism in the stories contained in the book collection of short stories by Ihan Sunrise. This study aims to describe the forms of discrimination against Acehnese women and gender equality in Ihan Sunrise’s works throught a collection of short stories by Rihon. The research method used is a qualititative descriptive method with a literature study approach. Based on data analysis, the results of this study show that the works in the collection of Rihon short stories contain elements of feminism. Discrimination of women in Aceh that occurred for years in social strata. The different treatment of women from men in community life has given birth of the Acehnese women’s feminist movement.